2011
DOI: 10.1111/j.1574-6941.2011.01137.x
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural land-use affects the nutritional quality of stream microbial communities

Abstract: We investigated how the lipid composition (fatty acids and sterols) of benthic microbial mats, which represent an important basal food resource for stream food webs, differs between tropical streams located in protected pristine and agricultural Cerrado savannah areas. The total microbial biomass and lipid composition differed significantly between pristine and agricultural streams in parallel with differences in water quality and hydrodynamic characteristics. Agricultural streams exhibited lower total biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 46 publications
1
25
0
1
Order By: Relevance
“…Moreover, exposed leaf material initially exhibited very low absolute N and P concentrations and molar N:P ratios compared to literature values (Wantzen et al, 2008), but accumulated N during the incubation, indicating that the incubated leaves acted as a substrate for microbial growth (Gessner et al, 1999;Stallcup et al, 2006). Effects of agricultural land use on microbial community composition and metabolism in tropical streams, such as decreases in bacterial and fungal biomass and heterotrophic activity, have been reported (Boëchat et al, 2011) and may also be the cause for land-use effects on microbial decomposition of leaf litter.…”
Section: Ecosystem Functioningmentioning
confidence: 98%
“…Moreover, exposed leaf material initially exhibited very low absolute N and P concentrations and molar N:P ratios compared to literature values (Wantzen et al, 2008), but accumulated N during the incubation, indicating that the incubated leaves acted as a substrate for microbial growth (Gessner et al, 1999;Stallcup et al, 2006). Effects of agricultural land use on microbial community composition and metabolism in tropical streams, such as decreases in bacterial and fungal biomass and heterotrophic activity, have been reported (Boëchat et al, 2011) and may also be the cause for land-use effects on microbial decomposition of leaf litter.…”
Section: Ecosystem Functioningmentioning
confidence: 98%
“…On the other hand, Müller-Navarra et al [20] found that lake trophic status (indicated by total phosphorus [P]) was negatively correlated to the amount of EPA and DHA in seston (per unit C). Agriculture and other human land uses tend to increase the nitrogen (N) and P available in downstream waters [19][21], and these nutrient increases are presumably influencing algal community dynamics (productivity and species composition) in these previous studies [19], [20]. Whether these changes in primary producer FA composition lead to variation among ecosystems in primary consumer FA composition has apparently not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Boëchat et al [19] found that agricultural streams had higher per-mass amounts of essential PUFAs in biofilms than pristine streams, although biofilms were overall less extensive in agricultural streams (i.e., agricultural streams had small amounts of high-quality biofilms). On the other hand, Müller-Navarra et al [20] found that lake trophic status (indicated by total phosphorus [P]) was negatively correlated to the amount of EPA and DHA in seston (per unit C).…”
Section: Introductionmentioning
confidence: 99%
“…surroundings (Anderson 2014). The prompt responses allow the rapid detection of changes or impacts happening in the watersheds and could be helpful to understand the effects of land use, providing supporting data for the conservation of endangered environments, such as biodiversity hotspots (Boëchat et al 2011). The water quality in Marola Lake was connected to climate events, which was observed in the PCA ordination that clearly separated dry and rainy seasons.…”
Section: Discussionmentioning
confidence: 89%